Batch Simultaneous Saccharification and Fermentation of Primary Sludge at Very High Solid Concentrations for Bioethanol Production - Mendes, Cátia V. T. (2023)
A sustainable industrial future involves the exploitation of renewable resources to obtain a wide diversity of products and energy and the decrease of waste generation. Primary sludge (PS) from pulp and paper mills is a lignocellulosic residue mainly consisting of cellulose and hemicelluloses that can be converted to bioethanol. In the present work, bioethanol was produced from untreated PS by simultaneous saccharification and fermentation (SSF). Studies were carried out on initial solid concentration, yeast inoculum percentage, cellulolytic enzyme dosage, and co-application of two enzyme complexes (cellulolytic NS 22192 and xylanolytic Cellic® HTec2, Bagsværd, Denmark). Increasing solid content up to 22% improved ethanol concentration (59.1 g L1), productivity (1.97 g L1 h1), and yield (86.3%); however, at the maximum solid concentration (28%), both yield and productivity decreased. At the highest solid concentration, a decrease of 33% in the cellulolytic enzyme dosage was observed (compared to reference enzyme loadings). The co-application of the two enzyme complexes had a positive effect on PS conversion efficiency. When a preliminary scale-up strategy was implemented from 50 mL to 2.5 L at 22% solids concentration, similar results were obtained despite the initial mixing difficulties of the heterogeneous system.